The Effect of Hypertension Exercise on Blood Pressure Reduction in Hypertensive Patients: A Literature Review - Juli Andiani; Riskatrianti; Nuraini Yulianti; Jihan Nabilah Yusuf; Lulu Khairiyah; Khoirunnisa Indriyani; Nur Azizah Diah Pitriani; Rheza Armadani Putra; Firdaus Panji Permana; Muhammad Huda; Bachtiar Safrudin (CV. CENDIKIA JENIUS INDONESIA, 2026)
Background: Hypertension is a global disease whose symptoms are often not perceived by patients, causing the condition to be frequently neglected. Therefore, simple interventions are needed to prevent and control hypertension, one of which is exercise Methods: This study employed a literature review method by searching articles in the Google Scholar and PubMed databases and applying predetermined inclusion criteria. Results: Based on ten reviewed articles, various types of exercise, including Tera gymnastics, hypertension exercise, aerobic exercise, and Prolanis exercise, were proven to effectively reduce blood pressure in patients with hypertension. Conclusion: Exercise interventions have been shown to reduce blood pressure and can therefore be used as a reference for the prevention and management of hypertension.